Spatial Analysis of WTU for Sustainable Agrarian Reform in TORA Sintang - Magfoedin, Moefid; Soemarno; Atikawati , Dini (Graduate School of Universitas Brawijaya, 2026)
This study analyzes appropriate land use planning based on the Designated WTU (Wilayah Tanah Usaha) within the framework of a Sustainable Agrarian Arrangement System, focusing on HPK Non-Productive areas designated as Agrarian Reform Object Land (TORA) in Sintang Regency. The research object is the TORA reserve sourced from HPK Non-Productive Sintang Regency, covering 14,310.42 ha, as per the allocation decree (SK) issued by the Ministry of Environment and Forestry (MoEF), located in 6 villages in Ketungau Tengah District and 4 villages in Ketungau Hulu District. This study uses a descriptive quantitative approach with IP4T data analysis to formulate land use schemes based on slope, elevation, and land capability to define WTU classes, combined with GIS-based spatial analysis to map land tenure, land use patterns, WTU distribution, and identify potential community land empowerment aligned with new growth areas in the Sungai Kelik border region. WTU analysis in PB IP4T Existing and PB IP4T SK TORA identified two primary classes: WTU Utama 1C and WTU Utama 1D, and two additional classes: Non-WTU and WTU Terbatas. Non-WTU: 506 parcels (304.95 ha) vs. 489 parcels (144.38 ha), difference: 17 parcels and 160.57 ha. WTU Terbatas: 4 parcels (20.59 ha) vs. 3 parcels (11.93 ha). WTU Utama 1C: 2,849 parcels (15,415.22 ha) vs. 2,846 parcels (14,055.08 ha). WTU Utama 1D: 19 parcels, area reduced from 132.08 ha to 88.04 ha Keywords: Spatial Analysis, Sustainable Agrarian Reform, WTU